Employee resourcing strategies and universities’ corporate image: A survey dataset - Hezekiah Olubusayo Falola; Olumuyiwa Akinrole Oludayo; Maxwell Ayodele Olokundun; Odunayo Paul Salau; Ayodotun Stephen Ibidunni; Ebe Igbinoba (Data in Brief, 2018)
The data examined the effect of employee resourcing strategies on corporate image. The data were generated from a total of 500 copies of questionnaire administered to the academic staff of the six (6) selected private Universities in Southwest, Nigeria, out of which four hundred and forty-three (443) were retrieved. Stratified and simple random sampling techniques were used to select the respondents for this study. Descriptive and Linear Regression, were used for the presentation of the data. Mean score was used as statistical tool of analysis. Therefore, the data presented in this article is made available to facilitate further and more comprehensive investigation on the subject matter. Keywords: Manpower planning, Employee attraction, Employee deployment, Employee retention, Corporate image